KOMUNIKASI POLITIK MUBALLIG DI KOTA PALU - Syamsuri Syamsuri; Suriati Suriati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
There are three social levels of Islamic preacher in Palu, ulama, ustaz and guru mengaji. The emergence of 'ulama (muslim scholars) on the political stage is an epicenter of social, cultural and economic dynamics. 'Ulama felt that they must interfere to guide Muslim community in politics in order to implement Islamic shari'a according to the Quran and Hadith. Political communication of Muslim preachers in Palu includes three steps: negotiation of political opportunity, consolidation of supports for candidates, and image building of da'wah message. Muslim preachers such as ulama, ustaz and guru mengaji are always drawn into politics at the season of political glamour, because they are considered as having loyal and pious mass basis.